And Jonah swam and swam and swam : Jonah's body in deep waters - Coetzee, Johan (Old Testament essays, 2004)
Within its present context the first 'prayer of Jonah' (Jonah 2) is embedded in various bodily issues relating to the rest of the narrative. The religious, societal, and personal bodies of the post-exilic Jews are under threat. In a nutshell, the first 'prayer of Jonah' reflects the relationship between these various bodies at play in the narrative.